Functional Nanohybrids and Nanocomposites Development for the Removal of Environmental Pollutants and Bioremediation - Giulia Rando; Silvia Sfameni; Maurilio Galletta; Dario Drommi; Simone Cappello; Maria Rosaria Plutino (Molecules, 2022)
World population growth, with the consequent consumption of primary resources and production of waste, is progressively and seriously increasing the impact of anthropic activities on the environment and ecosystems. Environmental pollution deriving from anthropogenic activities is nowadays a serious problem that afflicts our planet and that cannot be neglected. In this regard, one of the most challenging tasks of the 21st century is to develop new eco-friendly, sustainable and economically-sound technologies to remediate the environment from pollutants. Nanotechnologies and new performing nanomaterials, thanks to their unique features, such as high surface area (surface/volume ratio), catalytic capacity, reactivity and easy functionalization to chemically modulate their properties, represent potential for the development of sustainable, advanced and innovative products/techniques for environmental (bio)remediation. This review discusses the most recent innovations of environmental recovery strategies of polluted areas based on different nanocomposites and nanohybrids with some examples of their use in combination with bioremediation techniques. In particular, attention is focused on eco-friendly and regenerable nano-solutions and their safe-by-design properties to support the latest research and innovation on sustainable strategies in the field of environmental (bio)remediation.